On cayley isomorphisms of clifford semigroups - Sayan Panma (2018)
In this paper, we investigate the problem about determining for which Cayley graphs of a given Clifford semigroup are CI-graphs. We give sufficient conditions for Cayley graphs of Clifford semigroups to be CI-graphs and for Clifford semigroups to be CI-semigroups. © 2012 Academic Publications, Ltd.